An Analysis of Brand Image Implications to Consumer-Based Brand Equity: An Evidence of A Smartphone Product - Sari, Intan Tenisia Prawita; Rahayu, Agus; Hendrayati, Henny; Rauf, Mohamad Iqbal Abdul (Almana : Jurnal Manajemen dan Bisnis, 2024)
Companies are competing to maintain their market share and attract new consumers in this digital era. A deep understanding of how brand image influences Costumer Based Brand Equity is very important for companies to design effective marketing strategies. Therefore, this research aims to examine the influence of brand image on customer based brand equity. This research uses a quantitative approach. The respondents' responses indicated that all variable in brand image and CBBE of Samsung Brands in Garut Regency were very good. Furthermore, Brand association is proven to be the strongest indicator in building CBBE and brand loyalty is the least. there is a positive correlation between brand image and customer-based brand equity (CBBE).